(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Standard Operating Procedures (SOPs) have an important role in creating information transparency, improving work efficiency, minimizing errors, and supporting the development of educators and education personnel’s skills. This study uses a qualitative descriptive approach. The data used came from literature studies, direct observations, and interviews with administrative staff and teachers involved in school operations. The analysis process includes data reduction, data presentation, and conclusion drawing. The results of the analysis show that one of the components in managing administration in elementary schools to ensure the sustainability and quality of education is the Standard Operating Procedures or SOPs. Thus, a well-designed SOP is able to create information transparency, improve work efficiency, minimize errors, and support the development of the skills of educators and education personnel. The implementation of SOPs at SD IT Rocha Indonesia shows that although formal SOPs have not been fully implemented, initial steps such as digitization of archives, regular evaluations, staff training, and internal audits have supported more structured administrative management. Constraints such as technological limitations, manual attendance systems, and lack of formal guidelines can be overcome through the development of relevant SOPs and systematic implementation